Pulmonary Arterial Hypertension in Connective Tissue Diseases - Bodini, Bruno D.; Sitia, Simona; Tomasoni, Livio; Longhi, Matteo; Turiel, Maurizio (Current Respiratory Medicine Reviews, 2009)
Pulmonary arterial hypertension (PAH) is characterized by progressive obliteration of the small pulmonary vasculature leading to permanently increased vascular resistance and elevated pulmonary artery pressures over 25 mmHg at rest and 30 mmHg during exercise. Elevated pressures in the pulmonary circulation result in right heart failure and premature death. Besides idiopathic PAH, it can also occur in a variety of other conditions such as connective tissue diseases. Mainly patients suffering from systemic sclerosis, systemic lupus erythematosus and rheumatoid arthritis may be affected. In these patients, PAH may occur in association with left heart disease, interstitial fibrosis or as a result of an isolated pulmonary arteriopathy. The mechanisms leading to PAH remain unknown even if a pathophysiological model includes vasoconstrictor/vasodilator imbalance, thrombogenic factors, misguided angiogenesis and pro-inflammatory factors. Symptoms and clinical presentation are very similar to idiopathic PAH but mortality was confirmed to be higher. A 2-D echoDoppler examination is considered as the first-line diagnostic tool, however the results should be confirmed by right heart catheterization. Unfortunately, despite recent major improvements in PAH treatment, no current therapy can yet cure this devastating condition. Intravenous epoprostenol therapy has been proved to improve exercise capacity and symptoms in patients with systemic sclerosis. Also the endothelin receptor antagonists (bosentan and sitaxentan), the phosphodyesterase-type-5 inhibitor (sildenafil) and subcutaneous treprostinil have shown favourable results. Despite recent advances in treatment, PAH remains essentially untreatable even if pharmacological trials seem to slow down progression of the disease improving symptoms and quality of life of these patients.
Keywords: Pulmonary hypertension